Family history and DNA analysis in patients with suspected Huntington's disease. Issue 1 (1st July 2000) - Siesling, S; de Vlis, M Vegter-van; Losekoot, M; Belfroid, R D M; Maat-Kievit, J A; Kremer, H P H; Roos, R A C
Abstract : OBJECTIVES: Until recently a definite diagnosis of Huntington's disease could be made by a combination of clinical findings, a positive family history, and pathological confirmation. Prevalence data are based on these criteria. After finding the gene and its pathogenic mutation direct diagnostic confirmation became available. The aim of this study was to determine to what extent the direct assessment of CAG repeat length has allowed the diagnoses of additional patients, with atypical psychiatric or neurological disease, or those without a family history, that could otherwise not be diagnosed using traditional criteria. PATIENTS AND METHODS: From all 191 referred patients suspected of having Huntington's disease between July 1993 and January 1996 CAG repeat length was determined and the family history was reviewed in the Leiden roster. After a retrospective search the patients were subdivided in positive, negative, suspect, and unknown family histories. Patients with an expanded repeat (>35) were finally diagnosed as having Huntington's disease. The family history was compared with the repeat length and the clinical features. RESULTS: Clinical information was obtained for 172 patients. Of these, 126 patients had an expanded repeat, 77 had a positive, eight a negative, 40 a suspect, and one an unknown family history. Of the 44 patients with a normal repeat length four had a positive family history. Of the two patients with an intermediate repeat (between 30–36 repeats), one with a negative family history received a clinical diagnosis of Gilles de la Tourette's syndrome. The other had an unknown family history. CONCLUSION: Despite verification of the family history through the Leiden roster, many more patients and families could be diagnosed with the new approach than would have been possible with the traditional criteria. Because prevalence studies have been based on this type of information, the data suggest an underestimation of the prevalence of Huntington's disease in the community of 14%.